A hypnotic turbo-induction technique for wisdom tooth extraction. Issue 4 (3rd April 2023) - Schmierer, Albrecht; De Col, Leonardo; Stöcker, Thomas; Wolf, Thomas G.
ABSTRACT: The hypnotic turbo-induction technique has been used for more than three decades for various indications in dentistry and medicine. The use of the technique is described step by step using therapeutic communication and hypnotic suggestions in a dento-surgical treatment of a 48-year-old adult man. In a 15-minute appointment, two maxillary third molars (wisdom teeth) have been extracted without interruptions/complications by a dental team in a private practice trained in dental/medical hypnosis. The hypnotic turbo-induction technique proved to be a successful application method for anxiety reduction/relaxation, pain relief as well as postoperative wound healing after the extraction of wisdom teeth, which had to be extracted due to a medical indication. Anxiety- and pain reducing effects were noted by the patient during and after the treatment; rapid wound healing was noted by the dental team at the follow-up appointment one week later in this case. The cooperation of the two dental professionals trained in hypnosis proved to be beneficial, especially when the dentist must concentrate on the dento-surgical treatment, the dental assistant can concentrate on both the patient and the hypnosis and to maintain the hypnotic state by additional suggestions. Clinical research is needed to further investigate the effects of the proposed hypnotic turbo-induction technique.